ISLAM VERSUS TERORISME (Suatu Pendekatan Tafsir Hukum) - Ahmad Tholabi Kharlie (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2008)
Abstract: Islam Versus Terrorism: A Legal Qur’anic Exegesis Approach. In the last decade, terrorism discourse has become one of the most  important international issues. The West has claimed that Islam had supported terrorism and violence against other community, especially the West. This article attempts to elaborate the issue of terrorism in the context of Qur’anic exegesis and Islamic jurisprudence (fiqh). The author argues that Islam as the grace for the whole universe (rahmatan li al ‘âlamîn), in its very doctrines, never support terrorism, radicalism, violent actions, and destructive actions on the earth (fasâd fi al-ardh). This paper attempts to discuss how the Qur’an responses to the issue of terrorism by analyzing the interpretation of legal related verses. Kata Kunci: terorisme, tafsir hukum, al-irhâb, jihad, kekerasan.